2002
DOI: 10.1073/pnas.022652999
|View full text |Cite
|
Sign up to set email alerts
|

The fibrinolytic receptor for urokinase activates the G protein-coupled chemotactic receptor FPRL1/LXA4R

Abstract: The function of urokinase and its receptor is essential for cell migration in pathological conditions, as shown by the analysis of knockout mice phenotypes. How a protease of a fibrinolytic pathway can induce migration is not understood and no link between this protease and migration-promoting G protein-coupled receptors has been described. We now show that FPRL1͞LXA4R, a G protein-coupled receptor for a number of polypeptides and for the endogenous lipoxin A4 (LXA4), is the link between urokinase-type plasmin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
364
0
4

Year Published

2004
2004
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 329 publications
(372 citation statements)
references
References 32 publications
(55 reference statements)
4
364
0
4
Order By: Relevance
“…By contrast, microarray results showed that IL-10 increased mRNA levels of adhesion/migration-related genes such as L-selectin, VEGF receptor-1, t-PA, HM74, formyl peptide receptor-1 and lipoxin A4 receptor (Figure 3). The last three genes are involved in the synthesis of peptide receptors [38][39][40] that mediates leukocyte chemotaxis by binding peptides derived from protein degrada- tion occurring in damaged/diseased areas. 41 The overexpression of these receptors might play an important role in NK cell migration in response to the liberation of danger signals (eg peptides) freed in the tumor microenvironment.…”
Section: Genementioning
confidence: 99%
“…By contrast, microarray results showed that IL-10 increased mRNA levels of adhesion/migration-related genes such as L-selectin, VEGF receptor-1, t-PA, HM74, formyl peptide receptor-1 and lipoxin A4 receptor (Figure 3). The last three genes are involved in the synthesis of peptide receptors [38][39][40] that mediates leukocyte chemotaxis by binding peptides derived from protein degrada- tion occurring in damaged/diseased areas. 41 The overexpression of these receptors might play an important role in NK cell migration in response to the liberation of danger signals (eg peptides) freed in the tumor microenvironment.…”
Section: Genementioning
confidence: 99%
“…We found that soluble forms of uPAR, containing the 88 Ser-Arg-Ser-Arg-Tyr 92 sequence (uPAR [88][89][90][91][92] ), as well as the synthetic peptide Ser-Arg-Ser-Arg-Tyr (SRSRY), stimulates in vitro and in vivo angiogenesis in a protease-independent manner (13). The uPAR 88-92 sequence interacts with the formyl peptide receptors (FPR) type 1 and 2, henceforth inducing cell migration in an integrin-dependent manner (9,14,15). Upon binding to FPR, the synthetic peptide SRSRY causes FPR internalization and triggers vitronectin receptor activation with an inside-outside type of mechanism (16).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, uPAR can exist on the cell surface in either a three-domain form (D1D2D3), which is capable of binding uPA, or a two-domain form (D2D3), which does not bind uPA (5). Despite the lack of a transducing cytoplasmic tail, the uPA receptor is able to activate cell signaling pathways, probably by interacting with other cell surface proteins, such as integrins (7,8) and FMLP receptors (9,10), that interact with the cell interior (11).…”
mentioning
confidence: 99%